2011
DOI: 10.1038/mt.2010.314
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Design and Imaging Approaches to Visualize the Early Stages of Cellular Reprogramming

Abstract: Induced pluripotent stem cells (iPSCs) can be derived from somatic cells by gene transfer of reprogramming transcription factors. Expression levels of these factors strongly influence the overall efficacy to form iPSC colonies, but additional contribution of stochastic cell-intrinsic factors has been proposed. Here, we present engineered color-coded lentiviral vectors in which codon-optimized reprogramming factors are co-expressed by a strong retroviral promoter that is rapidly silenced in iPSC, and imaged the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
241
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 235 publications
(243 citation statements)
references
References 49 publications
2
241
0
Order By: Relevance
“…Western blot analysis from patient fibroblasts and CD3 + T cells demonstrated reduced protein expression compared with control (Henderson et al, 2013), and a PROVEAN score of 3.871 predicted this mutation to be deleterious. The cultured fibroblasts were reprogrammed to pluripotency by using an excisable, self-inactivating, codon-optimized lentiviral vector carrying OCT4, SOX2, KLF4, cMYC, and the reporter dTomato in a single cassette (Warlich et al, 2011). Immunofluorescence imaging and quantitative realtime PCR analysis confirmed the stemness of the generated iPSC line by expression of the characteristic pluripotency markers TRA-1-81, TRA-1-60, NANOG, OCT-4, SSEA-3, and SSEA-4 (Fig.…”
Section: Patient-derived Ipscs As An In Vitro Model For Rdmentioning
confidence: 99%
“…Western blot analysis from patient fibroblasts and CD3 + T cells demonstrated reduced protein expression compared with control (Henderson et al, 2013), and a PROVEAN score of 3.871 predicted this mutation to be deleterious. The cultured fibroblasts were reprogrammed to pluripotency by using an excisable, self-inactivating, codon-optimized lentiviral vector carrying OCT4, SOX2, KLF4, cMYC, and the reporter dTomato in a single cassette (Warlich et al, 2011). Immunofluorescence imaging and quantitative realtime PCR analysis confirmed the stemness of the generated iPSC line by expression of the characteristic pluripotency markers TRA-1-81, TRA-1-60, NANOG, OCT-4, SSEA-3, and SSEA-4 (Fig.…”
Section: Patient-derived Ipscs As An In Vitro Model For Rdmentioning
confidence: 99%
“…Since it has been shown recently that, contrary to the BAF complex in mouse stem cells, the BAF complex in human embryonic stem cells also contains Baf170 [29], and there might be differences in its functional conservation between mouse and human. To investigate the role of Brg1 and Baf155 in human reprogramming, we utilized a reprogramming cassette consisting of optimized human Oct4, Sox2, Klf4 and c-Myc along with a tomato reporter gene (SF hOSKM-idTomato) [30]. 100,000 F134 cells were infected with SF hOSKM-idTomato.…”
Section: Resultsmentioning
confidence: 99%
“…Human adult fibroblasts F134 [32] were reprogrammed with a lentiviral vector encoding the human cDNAs of OCT4, SOX2, KLF4 and c-MYC under the control of the SFFV promoter [30]. Retroviral vectors encoding Brg1 and Baf155 [2] and the lentiviral vector were…”
Section: Induction Of Oskm and Oskmbb Human Ips Cellsmentioning
confidence: 99%
“…Transduction of primary AML patient cells (0.35 3 10 6 ) was accomplished on a Retronectin (Takara Bio, Shiga, Otsu, Japan) coated 24-well plate with vesicular stomatitis virus glycoprotein-pseudotyped lentiviral vector particles encoding for the reprogramming cassette following standard protocols [2]. Three days after transduction, AML patient cells were transferred to a six-well plate containing irradiated murine embryonic fibroblasts and iPSC growth conditions according to published protocols [3].…”
Section: Significance Statementmentioning
confidence: 99%
“…We used a polycistronic 4-in-1 lentiviral vector to transfer the four Yamanaka reprogramming factors to generate iPSCs [2] from a pretherapy diagnostic bone marrow sample from a 29-year-old male patient with FAB M2 AML following informed consent according to the Declaration of Helsinki. Routine genetic analyses revealed that the AML sample had wild-type NPM1 and FLT3, contained no inv16/ t(16;16) or t(15;17) aberrations, but did harbor the t(8;21).…”
Section: Significance Statementmentioning
confidence: 99%